Literature Review on Patient Satisfaction in Antiretroviral Treatment Services - Wijaya, Dodi; Sari, Maya Mustika; Kurniawan, Dicky Endrian (Jurnal Kesehatan Komunitas Indonesia, 2023)
Satisfaction is a feeling of pleasure or disappointment arising from comparing the perceived performance of results/products with their expectations, and patient dissatisfaction with antiretroviral (ARV) treatment services will harm people with HIV/AIDS. This study aims to determine the level of satisfaction and the factors that influence satisfaction in ARV treatment services. This study uses a literature review with DOAJ, PubMed, ScienceDirect, and Springer databases. In 13 articles analyzed, two findings discussed the level of satisfaction and factors influencing patient satisfaction. The level of satisfaction with ARV treatment services is relatively high; on average, all patients are delighted. Factors influencing patient satisfaction are divided into sociodemographic, individual, nurse or health worker, health service, and environmental factors. Every country or every health service has different services; the level of satisfaction with ARV treatment services also varies because several factors influence it; it is necessary to improve the quality of service by improving the planning of facilities and infrastructure, good time management, arrangement of resources, facilities and work environment. Provide guidance and training to health workers. HIV/AIDS patients need not be afraid to seek treatment and are more open to expressing complaints to nurses or health workers.